(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2024)
The matachín dances are today recognized as a tradition in the city, thanks to the fact that their identity and cohesion have been perpetuated since the beginning of the 20th century. This sector of the community is characterized because their way of manifesting faith and religiosity is through dance and celebration. Both practices are intrinsically related, however, each one should be considered part of an object of study, therefore, this project focuses on the celebrations, specifically, at the time of the wake, since according to the informants there are approximately twelve dances that are carried out in the region, and if it is taken into account that the unofficial number of groups is around one hundred and fifty, a loss in the traditional practices is beginning to be evidenced. The method used was ethnographic, documenting the ritual processes that take place in the festivities in order to explore the ways of living the religiosity of both the community of dancers and those close to the group. Through field diaries, participant observation and in-depth interviews, it was identified that the relationship between the institutional canon and popular religiosity results in the generation of an imaginary of the Matachín community, which is not only manifested in the dancers, but also in the individuals who orbit around them.